Concomitant Infection of Helicobacter pylori and Intestinal Parasites: Burden, Sociodemographic and Clinical Characteristics in Hospitalized Children and Adolescents in Northern Lebanon [version 2; peer review: 1 approved, 2 approved with reservations] - Ghalia Khoder; Nour Mina; Sara Daher; Sara MINA (F1000Research)
Background Helicobacter pylori and intestinal parasites are well-known for their high prevalence in children, especially in developing countries. However, their concomitant infections are poorly documented. In this study, we aimed to evaluate the association between intestinal parasites and H. pylori among hospitalized children and adolescents with upper gastrointestinal complaints in Northern Lebanon. Methods A cross-sectional study was conducted involving 297 hospitalized pediatric patients, aged between 1 and 15 years, who presented with gastrointestinal symptoms. The socio-demographic, lifestyle, and gastrointestinal characteristics of all participants were analyzed. Fresh stool samples were collected and screened for the presence of intestinal parasites and H. pylori infections. Results 6.4% of the patients were positive for intestinal parasitic infections, 5.4% were positive for H. pylori infection, and 11.8% were co-infected. The results of the Chi-square test showed that H. pylori infection is significantly associated with parasitic infection but not with a particular species. The most frequent coinfection was H. pylori-Entamoeba histolytica (77.1%). Moreover, H. pylori infection was associated with overcrowding and infrequent washing of vegetables before eating. The prevalence of co-infections increased in patients of mothers with a primary educational level or less. In regards to clinical characteristics, our findings showed a statistically significant relationship between i) gastric reflux and H. pylori, and ii) severe diarrhea and parasitic infection. Conclusion Our data highlighted the association between H. pylori and intestinal parasitic infections. Thus, H. pylori detection could be taken into consideration while screening for parasitic infections in children and adolescents.